On the Upper Bounds of Test Statistics for a Single Outlier Test in Linear Regression Models - Tobias Ejiofor Ugah; Emmanuel Ikechukwu Mba; Micheal Chinonso Eze; Kingsley Chinedu Arum; Ifeoma Christy Mba; Henrietta Ebele Oranye (Journal of Applied Mathematics)
A bewildering large number of test statistics have been found for testing the presence of an outlier in multiple linear regression models. Exact critical values of these test statistics are not available, and approximate ones are usually obtained by the first-order Bonferroni upper bound or large-scale simulations. In this paper, we show that the upper bound values of two of these test statistics are algebraically the same. An application to real data for multiple linear regression is used to demonstrate the procedure.